Pengaruh Kebutuhan Aktualisasi Diri terhadap Potensi Bakat Siswa SMA Negeri 2 Kota Bengkulu - Ariani, Winda Ade; Kurniah, Reni; Jannah, Nurul (CV. Creative Tugu Pena, 2022)
The problem that is often faced by students is the problem of finding the potential talent that exists in them. In addition, the process of self-actualization that is not easy makes it difficult for teenagers to experience it. Talent is an innate ability that is more or superior which is a potential that still needs to be trained and developed. Self-actualization is the tendency to realize and develop the talents, capacities, and abilities of a human being. Academic self-actualization is self-actualization in the academic or educational field. This study aims to determine the effect of self-actualization on the talent potential of SMA Negeri 2 Bengkulu City students. The object of this research is the students of class X and XI science, totaling 100 people. The research variable consists of two variables, namely the independent variable is self-actualization and the dependent variable is the potential talent of students. The data collection method used is a Likert scale questionnaire. The data analysis method used is a simple linear regression analysis method. The results showed that the average level of student self-actualization was included in the very high category, this can be seen from the number of students who fall into that category as much as 65%. Based on the results of the study, there is a significant influence on the need for self-actualization on the potential talents of SMA Negeri 2 Bengkulu City students.